Altered miRNA Expression Due to Bisphenol A Exposure and Associated Health Implications: A Narrative Review - Sornali Rani Roy; Soumya Sunil Nair; Aamer Mohammed; Stephen L. Atkin; Edwina Brennan (Journal of Xenobiotics, 2026)
Bisphenol A (BPA) is a non-persistent industrial chemical widely used in the production of polycarbonate plastics and epoxy resins. Due to its mass production and versatility, BPA is ubiquitous in environmental matrices, leading to human exposure through ingestion, dermal contact, and inhalation. As a known endocrine-disrupting chemical (EDC) with estrogenic activity, BPA exposure has been associated with reproductive, metabolic, immune, oncogenic, and developmental effects. Mechanistically, BPA is reported to exert its toxic effects via multiple pathways, including alterations in epigenetic microRNA (miRNA) expression. miRNAs are endogenous non-coding RNA molecules that regulate gene expression by targeting mRNAs, thereby influencing a wide range of cellular and metabolic pathways involved in development and disease. Importantly, this review consolidates evidence suggesting that the biological effects of BPA may, in part, be mediated through miRNA-driven epigenetic modifications, affecting numerous downstream proteins and signaling pathways. Altered miRNA expression induced by BPA exposure is implicated in diverse health outcomes, including reproductive dysfunction, oncogenesis, metabolic disorders, and neurodevelopmental abnormalities. Notably, BPA exposure predominantly results in the upregulation of specific miRNAs, such as miR-21 and miR-146a, although tissue-specific and sex-dependent variations are evident. In this review, we provide a comprehensive overview of human, in vivo, and in vitro studies investigating BPA-induced miRNA dysregulation and its associated biological effects.